2022
DOI: 10.1007/s10552-022-01637-z
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and pancreatic cancer: a sex-specific analysis in the Multiethnic Cohort study

Abstract: Purpose To examine whether the detrimental smoking-related association with pancreatic cancer (PC) is the same for women as for men. Methods We analyzed data from 192,035 participants aged 45–75 years, enrolled in the Multiethnic Cohort study (MEC) in 1993–1996. We identified PC cases via linkage to the Hawaii and California Surveillance, Epidemiology, and End Results Program cancer registries through December 2017. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…20 Another group identified that current smoking was associated with risk of PC in a multiethnic cohort, a risk which increased with smoking duration and higher dosages. 21 The 2-year cumulative incidence of PC was 1.6% in our AP cohort, a risk over 23 times higher than that of the age-matched general population, based on results from Surveillance, Epidemi-ology, and End Results. 22 Despite the high mortality and morbidity from PC, screening all individuals in the general population for PC is not feasible given its rarity.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…20 Another group identified that current smoking was associated with risk of PC in a multiethnic cohort, a risk which increased with smoking duration and higher dosages. 21 The 2-year cumulative incidence of PC was 1.6% in our AP cohort, a risk over 23 times higher than that of the age-matched general population, based on results from Surveillance, Epidemi-ology, and End Results. 22 Despite the high mortality and morbidity from PC, screening all individuals in the general population for PC is not feasible given its rarity.…”
Section: Resultsmentioning
confidence: 76%
“…Pancreatic cysts were previously found to be present in nearly 50% of high-risk surveillance groups who progressed to PC 20 . Another group identified that current smoking was associated with risk of PC in a multiethnic cohort, a risk which increased with smoking duration and higher dosages 21 …”
Section: Discussionmentioning
confidence: 99%
“…These ndings are consistent to previous research. 33,34 Smoking is a known risk factor for PC as well as for disease progression in CP. 35 Furthermore, this study revealed that overweight, prediabetes or diabetes, gallstone disease, and hepatic brosis/cirrhosis were associated with an increased risk of PC among patients with pancreatitis, which is in line with a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking: Most publications agree that cigarette smoking represents an important risk factor for PDAC [ 92 , 93 , 94 , 95 , 96 , 97 ]. According to Silverman et al [ 98 ], eliminating cigarette smoking would decrease pancreatic cancer incidence by 27% in the United States.…”
Section: Part 1: Pancreatic Cancer Riskmentioning
confidence: 99%